Biphasic impacts of graphite-derived engineering carbon-based nanomaterials on plant performance: Effectiveness vs. nanotoxicity - Qingnan Wu; Chenjie Fan; Hezhong Wang; Yanlai Han; Fuju Tai; Jiakai Wu; Hui Li; Rui He (Advanced Agrochem, 2023)
Graphite-derived carbon-based nanomaterials (GCNMs) as an exciting class of engineering carbonmaterials have been extensively exploited in environment and agriculture for pollution restorer, environmental purifier, plant growth stimulant, and stress resistance inducer. With the increasing demand of production in past decades, GCNMs were inevitably released into the natural environment and became emerging pollutants.This review briefly summarized the recent progress on GCNMs-plant interaction with positive and negative sides, and discussed the biphasic (stimulatory-inhibitory) regulation of GCNMs on plant systems. The emphasis was placed on disseminating the latest scientific research, covering various effectiveness of GCNMs on plants and cells as well as nanotoxicity. Particularly, it is highlighted that fullerenes, carbon nanotubes, graphenes, and their functionalized forms as the representative zero-, one-, and two-dimensional GCNMs in optimum quantity have favorable efficacy on plants for seed germination, growth and development, fruit and productivity, and stress tolerance. On the contrary, GCNMs have possibly induced cytotoxicity and phytotoxicity on plant at anatomic, physiological, and genetic levels. The toxic mechanisms were mainly attributed to ion leakage from membrane, chloroplast damage, decreasing the levels of photosynthetic/nonphotosynthetic pigments and plant hormones, downregulating activities of metabolism and enzymatic/non-enzymatic antioxidant systems, or triggering ROS increase for inducing oxidative stress. This comprehensive review provides an in-depth insight of advanced progress made toward the utilization of GCNMs in plant science fields as well as current challenges. Future perspectives on a directional guide for further research in the emerging area of GCNMs-enabled phytonanotechnology are summarized at the end. This will possibly provide an important reference role for further study and rational application of GCNMs in agriculture.